Traumatic injury and multiple sclerosis: A systematic review and meta-analysis - Warren, Sharon (2017)
A systematic review/meta-analysis of literature addressing a possible association between traumatic injury and onset of multiple sclerosis was conducted. Medline, Embase, Cochrane DSR, Ovid HealthStar, CINAHL, ISI Web of Science and Scopus were searched for analytical studies from 1950 to 2011. Two investigators independently reviewed articles for inclusion, assessing their quality using the Newcastle-Ottawa Scale. Of the 13 case-control studies included, 8 were moderate quality and 5 low; of the 3 cohort studies 2 were high and 1 moderate. Meta-analysis including moderate and low quality case-control studies produced a modest but significant odds ratio: 1.41 (95% confidence interval: 1.03, 1.93). However, when low quality studies were excluded, the resulting odds ratio was non-significant. Cohort studies produced a non-significant standardized incidence ratio of 1.00 (95% confidence interval: 0.86, 1.16). These findings support the conclusion that there is no association between traumatic injury and multiple sclerosis onset; more high quality cohort studies would help to confirm this observation.